Enantioselective [3+3] atroposelective annulation catalyzed by N-heterocyclic carbenes - Zhao, Changgui; Guo, Donghui; Munkerup, Kristin; Huang, Kuo-Wei; Li, Fangyi; Wang, Jian (Nature communications, 2018)
Axially chiral molecules are among the most valuable substrates in organic synthesis. They are typically used as chiral ligands or catalysts in asymmetric reactions. Recent progress for the construction of these chiral molecules is mainly focused on the transition-metal-catalyzed transformations. Here, we report the enantioselective NHC-catalyzed (NHC: N -heterocyclic carbenes) atroposelective annulation of cyclic 1,3-diones with ynals. In the presence of NHC precatalyst, base, Lewis acid and oxidant, a catalytic C–C bond formation occurs, providing axially chiral α-pyrone−aryls in moderate to good yields and with high enantioselectivities. Control experiments indicated that alkynyl acyl azoliums, acting as active intermediates, are employed to atroposelectively assemble chiral biaryls and such a methodology may be creatively applied to other useful NHC-catalyzed asymmetric transformations. Axially chiral compounds are commonly found in nature. Here, the authors show the highly enantioselective construction of axially chiral biaryls via an N -heterocyclic carbenes-catalyzed [3+3] atroposelective annulation of ynals with cyclic 1,3-diones.